Trends in criminal policy: (dis) organising the chaos. Concept - Туляков, Вячеслав Олексійович; Туляков, В. О.; Tuliakov, Viacheslav O. (Ciudad Real, 2023)
• Criminal policy notion • Development of criminal policy (totalitarian vs democracy, punitive vs restorative) • International protection of human rights. New era, new priorities (persons, groups, states, world) • Metamodern methodology and criminal policy
Tuliakov V. О. Trends in criminal policy: (dis) organising the chaos. Concept [Electronic resource] : lecture 1 : [presentation PowerPoint] / V. О. Tuliakov. – Electronic data (14 slides). – Ciudad Real, 2023. – Режим доступу : https://hdl.handle.net/11300/25979
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; Criminal policy; International protection of human rights; Metamodern methodology